2019
DOI: 10.1111/crj.13079
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for COPD exacerbations and mortality in patients with overlap syndrome

Abstract: Introduction:Patients with chronic obstructive pulmonary disease (COPD) and obstructive sleep apnoea (OSA)-overlap syndrome-have a substantially greater risk of morbidity and mortality, compared to those with either COPD or OSA alone. Objectives: The aim of this retrospective study was to identify clinical modifiable factors associated with COPD exacerbations and all-cause mortality in patients with overlap syndrome. Methods:The electronic records of patients with simultaneous COPD and OSA who had a documented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…The same association has been explored in longitudinal studies and it is reported that BMI is an independent prognostic factor for COPD. 7 , 25 28 The Copenhagen City Heart Study reported that the risk of death in COPD increases with weight loss (RR 2.14 CI 95% :(1.18–3.89)), but not with weight gain (RR 0.95; CI 95% (0.43–2.08)). 25 …”
Section: Discussionmentioning
confidence: 99%
“…The same association has been explored in longitudinal studies and it is reported that BMI is an independent prognostic factor for COPD. 7 , 25 28 The Copenhagen City Heart Study reported that the risk of death in COPD increases with weight loss (RR 2.14 CI 95% :(1.18–3.89)), but not with weight gain (RR 0.95; CI 95% (0.43–2.08)). 25 …”
Section: Discussionmentioning
confidence: 99%
“…75,76 PAP therapy has been linked with physiological benefits in OS including improved arterial blood gases (reduced PaCO 2 and increased PaO 2 ), 28,32,77 6-minute walk distance, 78 forced expiratory volume in 1 second (FEV 1 ), 32,79 respiratory muscle strength, 80 skeletal muscle strength, 80 exercise capacity, 80 and mean pulmonary artery pressure. 81 Patients who are adherent to PAP therapy have been found to have reduced COPD exacerbations, 82 COPD-related hospitalizations, 46,83,84 cardiovascular events, 45 and mortality. 46,82,85,86 Most of these studies employed CPAP.…”
Section: Accepted Articlementioning
confidence: 99%
“…81 Patients who are adherent to PAP therapy have been found to have reduced COPD exacerbations, 82 COPD-related hospitalizations, 46,83,84 cardiovascular events, 45 and mortality. 46,82,85,86 Most of these studies employed CPAP. Patients with emphysema have been found to have lower CPAP adherence compared with obese patients with daytime sleepiness.…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the presence of the OS was associated with a high frequency of hospitalizations from COPD exacerbations, severe respiratory symptoms, and low quality of life. Thus, increasing all-cause mortality compared with those with just COPD alone [46,47]. Also, the incidence of acute respiratory failure in patients diagnosed with the OS is increased compared with either disease alone and correlated to nocturnal hypoxemia particularly in obese individuals.…”
Section: Clinical and Cardiovascular Consequencesmentioning
confidence: 99%